Male genitourinary schistosomiasis-related symptoms among long-term Western African migrants in Spain: a prospective population-based screening study - Sílvia Roure; Xavier Vallès; Olga Pérez-Quílez; Israel López-Muñoz; Anna Chamorro; Elena Abad; Lluís Valerio; Laura Soldevila; Sergio España; Alaa H. A. Hegazy; Gema Fernández-Rivas; Ester Gorriz; et al. (BMC, 2024)
Abstract Background Schistosomiasis is highly endemic in sub-Saharan Africa and frequently imported to Europe. Male urogenital manifestations are often neglected. We aimed to ascertain the prevalence of genitourinary clinical signs and symptoms among long-term African migrants in a non-endemic European country using a serology test. Methods We carried out a prospective, community-based cross-sectional study of adult male migrants from sub-Saharan Africa living in Spain. Schistosoma serology tests and microscopic urine examinations were carried out, and clinical data were obtained from an electronic medical record search and a structured questionnaire. Results We included 388 adult males, mean age 43.5 years [Standard Deviation (SD) = 12.0, range: 18-76]. The median time since migration to the European Union was 17 [Interquartile range (IQR): 11-21] years. The most frequent country of origin was Senegal (N = 179, 46.1%). Of the 338, 147 (37.6%) tested positive for Schistosoma. Parasite eggs were present in the urine of only 1.3%. Nine genitourinary clinical items were significantly associated with positive Schistosoma serology results: pelvic pain (45.2%; OR = 1.57, 95% CI: 1.0-2.4), pain on ejaculation (14.5%; OR = 1.85, 95% CI: 1.0-3.5), dyspareunia (12.4%; OR = 2.45, 95% CI: 1.2-5.2), erectile dysfunction (9.5%; OR = 3.10, 95% CI: 1.3-7.6), self-reported episodes of infertility (32.1%; OR = 1.69, 95% CI: 1.0-2.8), haematuria (55.2%; OR = 2.37, 95% CI: 1.5-3.6), dysuria (52.1%; OR = 2.01, 95% CI: 1.3-3.1), undiagnosed syndromic STIs (5.4%), and orchitis (20.7%; OR = 1.81, 95% CI: 1.0-3.1). Clinical signs tended to cluster. Conclusions Urogenital clinical signs and symptoms are prevalent among male African long-term migrants with a positive Schistosoma serology results. Genital involvement can be frequent even among those with long periods of non-residence in their sub-Saharan African countries of origin. Further research is needed to develop diagnostic tools and validate therapeutic approaches to chronic schistosomiasis. Graphical Abstract